210 Prognosis of Breast Cancer in Very Young Age (Less Than 30 Years). (4th May 2021) - Abid, M; Bano, R; Salim, M; Khan, A I; Chaudhry, M Z; Khan, H M
Abstract: Background: Breast cancer diagnosed at younger age has aggressive biology being triple negative and high grade and associated with poor prognosis. Method: Retrospectively data of 121 patients age 30 years or younger registered during the year 2008 was reviewed. Demographics studied were age at diagnosis, gender, pregnancy, or lactation associated, family history, histopathological diagnosis, stage of the disease, receptors, type of treatment, response, local recurrence, distant relapse, survival. Results: One patient was male. Age range 20 -30 years, single patient had bilateral involvement. half 50.4%(n = 61) patients had locally advanced disease at presentation. Pregnancy/ lactation associated breast cancer was seen in 29.8%(n = 36). Most common stage was stage III (52.1%) & stage II (33.9%). IDC was the most common histology 94.2% (n = 114) Triple negative was most common molecular subtype present in 46.3%(56). After 5 years follow up, local recurrence was observed in 12.4%(n = 15), cancer related deaths were 42.1%(n = 51). Conclusions: Breast cancer in very young has very aggressive tumor biology, needs aggressive treatment with surgery, chemotherapy, radiation therapy and hormonal therapy, furthermore there is need to identify possible environmental factors which may contribute in the rising incidence in this age group.